PENGARUH BIMBINGAN MENYIKAT GIGI TEKNIK FONES MENGGUNAKAN VIDEO TUTORIAL TERHADAP KETERAMPILAN MENYIKAT GIGI ANAK PRASEKOLAH (Jurnal Kesehatan Siliwangi, 2021)
In 2018, 96.8% of people in West Java Province had the habit of brushing their teeth every day and only 2.8% of the time they brush their teeth are correct. The concept of dental and oral nursing care, every child should get guidance on brushing teeth which is carried out continuously (continuously), especially for children who do not have the ability to brush their teeth properly. Knowing the effect of guidance on brushing teeth using the fones technique using video tutorials on brushing skills in preschool children. This type of research is Analytical with Quasi Experimental. The sampling technique used total sampling (32 respondents), after that the resulting data was processed by data analysis using the Wilcoxon test. Research shows that preschool children in Garut Regency kindergarten after being given guidance on brushing their teeth using the fones technique using video tutorials as many as 17 respondents or (53.1%) have good criteria. This shows that there is a significant effect of guidance on brushing teeth using video tutorials on the skills of preschool children at Garut Regency kindergarten. It is known that there is an influence from the guidance of brushing teeth with the technique of fones on the skills of preschool children at Garut Regency kindergarten.